Applying tDCS over the dominant Hemisphere to observe event-related Desynchronization - Khan, Akif Ahmed; Bastob, Abu Wakkas; Ahmed, Bushra; Reza, Abdullah Al (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.